Purgatory [compact disc] - Childers, Tyler, 1991- (Hickman Holler Records, 2017)
Like many great Southern storytellers, singer-songwriter Tyler Childers has fallen in love with a place. The people, landmarks, and legendary moments from his childhood home of Lawrence County, Kentucky, populate the ten songs in his formidable debut, an album that's simultaneously modern and as ancient as the Appalachian Mountains in which events unfold.